The effect of surface charge on nonspecific uptake and cytotoxicity of CdSe/ZnS core/shell quantum dots - Breus, Vladimir V.; Pietuch, Anna; Tarantola, Marco; Basché, Thomas; Janshoff, Andreas (Beilstein Journal of Nanotechnology, 2015)
In this work, cytotoxicity and cellular impedance response was compared for CdSe/ZnS core/shell quantum dots (QDs) with positively charged cysteamine–QDs, negatively charged dihydrolipoic acid–QDs and zwitterionic D-penicillamine–QDs exposed to canine kidney MDCKII cells. Pretreatment of cells with pharmacological inhibitors suggested that the uptake of nanoparticles was largely due to receptor-independent pathways or spontaneous entry for carboxylated and zwitterionic QDs, while for amine-functionalized particles involvement of cholesterol-enriched membrane domains is conceivable. Cysteamine–QDs were found to be the least cytotoxic, while D-penicillamine–QDs reduced the mitochondrial activity of MDCKII by 20–25%. Although the cell vitality appeared unaffected (assessed from the changes in mitochondrial activity using a classical MTS assay after 24 h of exposure), the binding of QDs to the cellular interior and their movement across cytoskeletal filaments (captured and characterized by single-particle tracking), was shown to compromise the integrity of the cytoskeletal and plasma membrane dynamics, as evidenced by electric cell–substrate impedance sensing.
Keywords: biocompatibility; CdSe/ZnS; cytotoxicity; ECIS; quantum dots; single-particle tracking

(untitled) - Wu, P.; Yan, X.-P. (Chem. Soc. Rev., 2013)

(untitled) - Xu, J.-J.; Zhao, W.-W.; Song, S.; Fan, C.; Chen, H.-Y. (Chem. Soc. Rev., 2014)

(untitled) - Yasui, T.; Kaji, N.; Baba, Y. (Annu. Rev. Anal. Chem., 2013)

(untitled) - Zhu, Y.; Hong, H.; Xu, Z. P.; Li, Z.; Cai, W. (Curr. Mol. Med., 2013)

(untitled) - Chinnathambi, S.; Chen, S.; Ganesan, S.; Hanagata, N. (Adv. Healthcare Mater., 2014)

(untitled) - Wu, P.; Zhao, T.; Wang, S.; Hou, X. (Nanoscale, 2014)

(untitled) - Winnik, F. M.; Maysinger, D. (Acc. Chem. Res., 2013)

(untitled) - Cho, S. J.; Maysinger, D.; Jain, M.; Roder, B.; Hackbarth, S.; Winnik, F. M. (Langmuir, 2007)

(untitled) - Derfus, A. M.; Chan, W. C. W.; Bhatia, S. N. (Nano Lett., 2004)

(untitled) - Kirchner, C.; Liedl, T.; Kudera, S.; Pellegrino, T.; Muñoz Javier, A.; Gaub, H. E.; Stölzle, S.; Fertig, N.; Parak, W. J. (Nano Lett., 2005)

(untitled) - Hoshino, A.; Fujioka, K.; Oku, T.; Suga, M.; Sasaki, Y. F.; Ohta, T.; Yasuhara, M.; Suzuki, K.; Yamamoto, K. (Nano Lett., 2004)

(untitled) - Gao, X.; Cui, Y.; Levenson, R. M.; Chung, L. W. K.; Nie, S. (Nat. Biotechnol., 2004)

(untitled) - Pellegrino, T.; Manna, L.; Kudera, S.; Liedl, T.; Koktysh, D.; Rogach, A. L.; Keller, S.; Rädler, J.; Natile, G.; Parak, W. J. (Nano Lett., 2004)

(untitled) - Selvan, S. T.; Tan, T. T.; Ying, J. Y. (Adv. Mater., 2005)

(untitled) - Gerion, D.; Pinaud, F.; Williams, S. C.; Parak, W. J.; Zanchet, D.; Weiss, S.; Alivisatos, A. P. (J. Phys. Chem. B, 2001)

(untitled) - Bruchez, M., Jr; Moronne, M.; Gin, P.; Weiss, S.; Alivisatos, A. P. (Science, 1998)

(untitled) - Ryman-Rasmussen, J. P.; Riviere, J. E.; Monteiro-Riviere, N. A. (J. Invest. Dermatol., 2007)

(untitled) - Lovrić, J.; Bazzi, H. S.; Cuie, Y.; Fortin, G. R. A.; Winnik, F. M.; Maysinger, D. (J. Mol. Med. (Heidelberg, Ger.), 2005)

(untitled) - O Choi, A.; Cho, S. J.; Desbarats, J.; Lovrić, J.; Maysinger, D. (J. Nanobiotechnol., 2007)

(untitled) - Chang, E.; Thekkek, N.; Yu, W. W.; Colvin, V. L.; Drezek, R. (Small, 2006)

(untitled) - Male, K. B.; Lachance, B.; Hrapovic, S.; Sunahara, G.; Luong, J. H. T. (Anal. Chem., 2008)

(untitled) - Giaever, I.; Keese, C. R. (Proc. Natl. Acad. Sci. U. S. A., 1984)

(untitled) - Reiss, B.; Janshoff, A.; Steinem, C.; Seebach, J.; Wegener, J. (Langmuir, 2003)

(untitled) - Janshoff, A.; Kunze, A.; Michaelis, S.; Heitmann, V.; Reiss, B.; Wegener, J. (J. Adhes. Sci. Technol., 2010)

(untitled) - Tarantola, M.; Pietuch, A.; Schneider, D.; Rother, J.; Sunnick, E.; Rosman, C.; Pierrat, S.; Sönnichsen, C.; Wegener, J.; Janshoff, A. (Nanotoxicology, 2011)

(untitled) - Tarantola, M.; Schneider, D.; Sunnick, E.; Adam, H.; Pierrat, S.; Rosman, C.; Breus, V.; Sönnichsen, C.; Basché, T.; Wegener, J.; Janshoff, A. (ACS Nano, 2009)

(untitled) - Tarantola, M.; Sunnick, E.; Schneider, D.; Marel, A. K.; Kunze, A.; Janshoff, A. (Chem. Res. Toxicol., 2011)

(untitled) - Ruan, G.; Agrawal, A.; Marcus, A. I.; Nie, S. (J. Am. Chem. Soc., 2007)

(untitled) - Tada, H.; Higuchi, H.; Wanatabe, T. M.; Ohuchi, N. (Cancer Res., 2007)

(untitled) - Michalet, X.; Pinaud, F. F.; Bentolila, L. A.; Tsay, J. M.; Doose, S.; Li, J. J.; Sundaresan, G.; Wu, A. M.; Gambhir, S. S.; Weiss, S. (Science, 2005)

(untitled) - Nan, X.; Sims, P. A.; Chen, P.; Xie, X. S. (J. Phys. Chem. B, 2005)

(untitled) - Algar, W. R.; Krull, U. J. (ChemPhysChem, 2007)

(untitled) - Breus, V. V.; Heyes, C. D.; Tron, K.; Nienhaus, G. U. (ACS Nano, 2009)

(untitled) - Rejman, J.; Oberle, V.; Zuhorn, I. S.; Hoekstra, D. (Biochem. J., 2004)

Exocytosis and Endocytosis - Ivanov, A. I. (Pharmacological Inhibition of Endocytic Pathways: Is It Specific Enough to Be Useful?, 2008)

(untitled) - Sage, D.; Neumann, F. R.; Hediger, F.; Gasser, S. M.; Unser, M. (IEEE Trans. Image Process., 2005)

(untitled) - Bannai, H.; Lévi, S.; Schweizer, C.; Dahan, M.; Triller, A. (Nat. Protoc., 2007)

(untitled) - Courty, S.; Luccardini, C.; Bellaiche, Y.; Cappello, G.; Dahan, M. (Nano Lett., 2006)

(untitled) - Seitz, A.; Surrey, T. (EMBO J., 2006)

(untitled) - Pierobon, P.; Achouri, S.; Courty, S.; Dunn, A. R.; Spudich, J. A.; Dahan, M.; Cappello, G. (Biophys. J., 2009)

(untitled) - Nelson, S. R.; Ali, M. Y.; Trybus, K. M.; Warshaw, D. M. (Biophys. J., 2009)

(untitled) - Mehta, A. D.; Rock, R. S.; Rief, M.; Spudich, J. A.; Mooseker, M. S.; Cheney, R. E. (Nature, 1999)

(untitled) - Rief, M.; Rock, R. S.; Mehta, A. D.; Mooseker, M. S.; Cheney, R. E.; Spudich, J. A. (Proc. Natl. Acad. Sci. U. S. A., 2000)

(untitled) - Inal, J.; Miot, S.; Schifferli, J. A. (Exp. Cell Res., 2005)

(untitled) - von Delwig, A.; Bailey, E.; Gibbs, D. M.; Robinson, J. H. (Eur. J. Immunol., 2002)

(untitled) - Orlandi, P. A.; Fishman, P. H. (J. Cell Biol., 1998)

(untitled) - Mahler, B.; Spinicelli, P.; Buil, S.; Quelin, X.; Hermier, J.-P.; Dubertret, B. (Nat. Mater., 2008)

(untitled) - Schneider, D.; Tarantola, M.; Janshoff, A. (Biochim. Biophys. Acta, Mol. Cell Res., 2011)

(untitled) - Wegener, J.; Abrams, D.; Willenbrink, W.; Galla, H. J.; Janshoff, A. (BioTechniques, 2004)

(untitled) - Wegener, J.; Keese, C. R.; Giaever, I. (Exp. Cell Res., 2000)